Care poverty among older adults in East Asia: A comparison of unmet care needs between China and Taiwan. (September 2022) - Hu, Bo; Chou, Yueh-Ching
Highlights: Older adults' unmet long-term care needs in china and taiwan were compared. Care poverty concept/Andersen's behavior model were employed for the comparison. The care poverty rate in IADL was lower in taiwan than in china. Unmet needs were driven by different factors between two groups of older adults. LTC services should meet the IADL care needs in both china and taiwan. Abstract: Purpose: Applying the concept of care poverty and Andersen's Behavior Model, this study compares the patterns of unmet long-term care needs and investigates the association between unmet needs and the depression and life satisfaction of older adults aged ≥ 65 in China and Taiwan that belong to the same East Asia welfare model. Methods: Data come from the 2015 China Health and Retirement Longitudinal Survey ( N  = 6, 341) and the 2015 Taiwan Longitudinal Study on Ageing ( N  = 4, 588). Results: Older adults in China and Taiwan differ significantly in terms of demographic and socioeconomic characteristics. The care poverty rate in activities of daily living (ADL) in these two Asian societies was similar and the rate in instrumental activities of daily living (IADL) was lower in Taiwan than in China. Regression analyses showed that unmet care needs were associated with different predisposing and enabling factors between older Chinese (e.g., residential area and marital status) and Taiwanese (e.g., living arrangement and frequency of seeing children) adults, but the association between depressive symptoms and life satisfaction and unmet care needs were highly similar based on comparison of correlation coefficients. Conclusions: Chinese disadvantaged older adults facing a higher risk of unmet care needs were those who were single and lived in rural areas, while Taiwanese were those who lived alone and had no close relationship with children. Additionally, long-term care services should meet the IADL care needs but not be limited to only meeting ADL care needs in both China and Taiwan.